2006
DOI: 10.1111/j.2006.0030-1299.15014.x
|View full text |Cite
|
Sign up to set email alerts
|

Size and temperature dependent foraging capacities and metabolism: consequences for winter starvation mortality in fish

Abstract: The foraging related capacities, energy requirements and the ability of individuals to withstand starvation are strongly dependent on body size and temperature. In this study, we estimated size‐dependent foraging rates and critical resource density (CRD) in small Arctic char (Salvelinus alpinus) under winter conditions and compared these with previous observations under summer conditions. We investigated if starvation mortality is size‐dependent in the laboratory, and we assessed the potential for winter growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
111
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 57 publications
8
111
0
Order By: Relevance
“…synthesis of HSPs may affect the immune functions of organism. Moreover, the metabolic rate and energy depletion of fish in winter is much lower than any other season [31]. Therefore, the present reduced induction of HSP70 expressions in the repeated handled carp post bacterial challenge may also be partially responsible for the increased disease insistence and the improved immune response.…”
Section: Discussionmentioning
confidence: 97%
“…synthesis of HSPs may affect the immune functions of organism. Moreover, the metabolic rate and energy depletion of fish in winter is much lower than any other season [31]. Therefore, the present reduced induction of HSP70 expressions in the repeated handled carp post bacterial challenge may also be partially responsible for the increased disease insistence and the improved immune response.…”
Section: Discussionmentioning
confidence: 97%
“…The excess synthesis of HSPs may affect the immune functions of organism. Moreover, the metabolic rate and energy depletion of fish in winter is much lower than any other season [38]. Therefore, the present reduced induction of HSP70 expressions in the repeated handled fish post bacterial challenge may also be partially responsible for the increased disease insistence and the improved immune responses.…”
Section: Discussionmentioning
confidence: 98%
“…When differently sized individuals of the same species compete for resources, the smaller individuals may therefore have an advantage (Persson 1985; figure 4f ) if they can grow and sustain themselves at a lower resource level than larger conspecifics (Lundberg & Persson 1993;Persson et al 1998). Mesocosm and in situ experiments have shown that the metabolic demands of Arctic Char increase with temperature at a faster rate than their foraging capacity (Bystrom et al 2006). If warming increases CRD disproportionately for larger individuals, adaptive foraging by exploiting a larger size range of prey might be able to mitigate these energetic requirements (figure 4g).…”
Section: Linking Across Spatio-temporal Scales and Levels Of Organizamentioning
confidence: 99%
“…The ability to gain energy can be separated into two size-dependent components: the search efficiency (encounter rate, attack rate) and the capacity to process food (handling; Lundberg & Persson 1993;Persson et al 1998): together these make up the foraging capacity of an individual (Bystrom & Andersson 2005;Bystrom et al 2006). The results of recent studies have revealed how complex food webs can arise from simple rules related to FT (Beckerman et al 2006;Petchey et al 2008), but the effects of temperature are yet to be fully incorporated in these new models, despite its strong influence on foraging rates (e.g.…”
Section: Linking Across Spatio-temporal Scales and Levels Of Organizamentioning
confidence: 99%